Environmental Reporting and Disclosure Practices - In Malaysian Property Industry - Natthondan, Shankari (2009)
This research examined and analyzed the extent of environmental reporting and disclosure practices of the Kuala Lumpur Composite Index Companies (KLCI) as listed on the Bursa Malaysia on 21 January 2008. In particular the property industry companies were identified as a high profile sector as it is more sensitively exposed to environmental activities. The degree of reporting on environmental matters by this category of listed companies is indicative of the trend of the overall compliance and perception of reporting level on the environmental reporting . A rating score card system was utilised to evaluate the extent of the environmental disclosures from the comprehensive information disclosed in the Corporate Annual Report announced and filed in the fiscal year 2007 by the 100 companies of the Kuala Lumpur Composite Index listed companies. The interpretation of the studied data and the scores point was further evaluated to identify if the ‘high profile’ property industries had a higher level of environmental financial disclosure as what would normally be associated with a more environmentally impacted industry. The finding suggested that for the Property Industry, there was lower than expected disclosure conformities and correlation between compliancy and operating revenue, number of employee, market capital , gearing and Total Asset. It should be noted that only source of data used was that of the Corporate AnnualReports and that no other references to public statement made from the Company itself or published articles, materials from external parties (Government Authorities, non-governmental organization, NGO, and such) were made use of during the analysis of this study. Although any accompanying documents with the issuance of Annual Report was used for the evaluation purpose ,for instance the “Sustainability Report” by the YTL Corporation Berhad to enable it’s stakeholders to be able to assess on better quantified sustainability reports on the group’s activity. In this dissertation paper, the terminology reference of companies as global corporate citizens is used as indicative and recognition of a resource constrained world to even the small show the significance of the inter relationship of being an small timber logging company in Brazil’s deforestation in South America and the impact of that small Brazilian company’s action on to the global warming changes that are affecting both hemispheres of the world. All companies can no longer be treated in geographical isolation as their business presence may not be global but their environmental impact is felt globally. This may be through direct contact or indirectly through supply chains, various stake holders connected to the company. The second phrase of corporate is obviously picked to denote it’s separate legal entity status and its fiduciary responsibility to its many stakeholders in trust and confidence. The corporate is bound by mandatory statutory obligations that are implemented in their country of operations. In this paper, we restrict our analysis of these mandatory statutory and common law compliance to it’s financial elements only. The reason being as the Laws and regulation slowly merge toward a one vision goal, these regulatory law will eventually unified such as what is taking place in the accounting standards on how financial statements of a corporate body located anywhere in the world , will eventually be bound by the same accounting standards and interpretation guidelines laid down by the International Financial Reporting Standards(IFRS) as governed by the International Accounting Standard Board (IASB). Finally, as citizens to denote that no one enterprise can be considered mutually exclusive and as citizens of the world, they owe certain amount of discretionary rights and responsibilities to other fellow world citizens.